The cross as metaphor for cross-cultural education - Van den Akker, Jose (Tamkang University, 2010)
The futurist employs time, especially future time, to transform the present. And 'when we get the direction right, that is 50 % of the story' (Inayatullah, 2009). This article is written for educators whose cross-cultural contexts challenge them to go beyond traditional forms of theory, presentation and method and face another direction. Ancient shapes such as the dot, the circle, the cross and the square (Chevalier & Gheerbrant, 1996) are neutral in themselves but culturally interpreted. Though the 'cross' is neutral in itself, cross-culturally it represents the dominant litany of Western theory, the masculinist myth of a unidirectional world, and the idea that crucifixion comes first and hope and transformation second. Cross-cultural education ignores the impact of the 'cross', which if surrounded with the circle symbolises the Earth (Milojevic, 1999) as Gaia (Lovelock, 2001). This cultural blindness frustrates educational change. A focus on the cross and the dynamics at its heart opens the gaze to the space between in an eye to eye (I to I) meeting: the 'cross' becomes a 'tracking device' and like an hourglass, an unlimited device for people to move through and out of geophilosophical baggage and into a fresh and open space.